Psychological and Linguistic Perspectives on ELT: Implications of Learning Theories on Language Acquisition (International Journal of Food and Nutritional Sciences, 2019)
English language teaching can be described as a means of control that applies hypotheses or useful territories of work established in bigger hypothetical directions. These hypothetical directions or the profound structures of ELT must be comprehended. This causes us to be better educated as teachers regarding the kind of choices we, and other stakeholders in education, settle on. We have options in all that we do in the teaching-learning cycle, and we need to fully comprehend what our decisions involve, from where our decisions are established, and what presumptions we hold when we settle on our decisions. As such, we will perceive how hypotheses and practice are connected.This paper concerns the hypothetical contemplations that have dominated ELT in its development as an order of study. It acquaints us with the directions or points of view fundamental to its examination, psychological linguistics, and sociological and historical orientations. These conversations are directed at two levels; 1) the worldwide or Western level, from where many ELT hypotheses originate, and 2) the particular degree of the Indian setting, where improvements are applied in useful terms.